Allelopathic activity of the picocyanobacterium Synechococcus sp. on unicellular eukaryote planktonic microalgae - Śliwińska-Wilczewska S. (2018)
The production and release of allelopathic compounds is an important adaptation by which some species of cyanobacteria can achieve a competitive advantage over other primary producers. In the present study we tested the allelopathic activity of the picocyanobacterium Synechococcus sp. against the following coexisting unicellular eukaryote microalgae: Porphyridium purpureum, Stichococcus bacillaris, Prymnesium parvum and Nitzschia dissipata. With these species, we covered a wide range of taxonomic groups. We demonstrated that both the addition of Synechococcus sp. cell-free filtrate and coculture inhibited the growth, chlorophyll content and photosynthetic rate of P. purpureum and S. bacillaris. Conversely, P. parvum, a well-known mixotroph, was positively affected by both Synechococcus sp. treatments. In contrast, N. dissipata was not affected by either the picocyanobacterial filtrate or coculture. These results suggest that the negative allelopathic effect is related to a reduction in the photosynthetic rate, and that Synechococcus sp. allelopathy should be taken into account in the interactions between picocyanobacteria and eukaryote competitors coexisting in a planktonic system. © CSIRO.